2015
DOI: 10.4103/0973-1482.147703
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oral leukoplakia with photodynamic therapy: A pilot study

Abstract: There was satisfactory reduction in the size of the OL lesion without any side-effects. Thus, ALA mediated PDT seems to be a promising alternative for the treatment of OL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 0 publications
0
43
0
2
Order By: Relevance
“…The selected studies were clinical and had a prospective design with a range between two and 147 individuals (Tables and ) . Twelve studies reported a mean age of study participants of between 50 and 67 years (age range: 27‐99 years) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected studies were clinical and had a prospective design with a range between two and 147 individuals (Tables and ) . Twelve studies reported a mean age of study participants of between 50 and 67 years (age range: 27‐99 years) .…”
Section: Resultsmentioning
confidence: 99%
“…In some of the studies, oral PMDS were OL, OE, OEL, OVH, OSMF, and OLP, in which PDT treatment has been undertaken . The total number of premalignant lesions reported in these studies was 815, with a range between five and 225 lesions . Twelve studies reported 465 patients with malignant lesions of the head and neck region who were underwent PDT treatment .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the study is to treat patients with OL using PDT in which 5-aminolevulinic acid (ALA) is used as a photosensitizer. Selvam NP, Sadaksharam J, Singaravelu G, Ramu R. [7] were included five patients with OL. They were treated with 10% ALA mediated PDT (light source: Xenon lamp, power: 0.1 W, wavelength: 630 ± 5 nm, total dose: 100 J/cm 2 per session) for 6-8 sessions.…”
Section: Treatment Methodsmentioning
confidence: 99%